Inventory of Drug Plant In Estuary Village Siberut District Siberut Southregency of Mentawai Islands - Des M; Gustina Indriati; Swandi Sakerengan (UNIVERSITAS NEGERI PADANG, 2017)
Traditional treatment is something that can not be separated from the life of the Mentawai people, especially the village of Muara Siberut South Siberut District since been entrenched in people's lives. The shift in value to knowledge about medicinal plants is beginning to be felt increasingly minimal, especially in the younger generation. This study aims to inventory medicinal plants as well as properties and how to use them, in the hamlet of Puro and Peigu hamlet, village of Muara Siberut District of South Siberut. The research was conducted by using Survey method and interview. The results of the study found 95 species of medicinal plants from 37 families are used to treat 39 kinds of diseases. The most common species found in the Zingiberaceae family are 12 species, F. Euphorbiaceae 9 species, F.Graminae and F.Compositae 8 species, F.Araceae, F.Acanthaceae, F.Orchidaceae, F.Piperaceae, and F.Rubiaceae respectively. each 4 species. For other families each 3 types, 2 types and 1 type. Of the 95 species of plants are 23 species have been cultivated in the yard of houses, and 72 species found wild in the yard and in the forest. In its use 65 species are used in singular form and 30 species are used in the form of herbs. It can be concluded that medicinal plants in Puro and Peigu hamlets are dominated by familia Zingiberaceae, familia Euphorbiaceae, familia Graminae and familia Compositae.Keywords: Inventory, Medicinal plants, Puro hamlet, Peigu hamlet, South Siberut